Arkiv i rörelse: Malmö, radikalism och arbetarrörelsens minnespolitik - Egefur, Fredrik (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2025)
What is included in the concept of the “labour movement”? And who holds the power to define its history? This article interrogates these issues in relation to a documentation project at the Labour Movement Archives in Skåne, where radical movements in Malmö – from autonomous networks to feminist and anti-racist initiatives – are collected and preserved for the future. The project raises questions about the archive’s role as a boundary-making institution: which narratives are preserved, which are lost, and how are these processes shaped by the labour movement’s historical and ideological frameworks? By exploring archival practice at the intersection of activism, historical writing, and institutional power, the article discusses how archives can both exclude and make space for new voices – and how an intersectional and critical approach can contribute to a more inclusive and socially relevant labour movement archive today.